Reflexivity in Digital Contexts: Perspectives from Ethnographic Research among Young Afghans in the Swiss Asylum System - Khamsy, Nina (Swiss Journal of Sociocultural Anthropology, 2025)
This article presents the essential input of reflexivity for conducting ethnographic research in digital contexts to highlight how power relations are articulated with digital practices. Drawing on fieldwork conducted between 2021 and 2022 among young Afghans in the Swiss asylum system, this paper examines how precarious legal statuses, such as those associated with temporary permits, shape digital practices and uses of Information and communications technology (ICT). By analysing online content and digital interactions collaboratively with my research participants, the study highlights how empowerment and surveillance mechanisms intertwine at transnational scales that contextualise digital practices. The diversity of shared media content is shaped by young people’s attunement to their audiences, their own precarious status, and sociopolitical dynamics, which, for this population, are impacted by the deterioration of the situation in Afghanistan since August 2021, as well as by institutional mistrust and the economic constraints they face in Switzerland.